Composição química e avaliação da atividade antimicrobiana do óleo essencial das folhas de Pimenta pseudocaryophyllus (Gomes) Landrum - Rosas, Elaine Cristina (2015)
The vegetables are widely used in homemade preparations and constitute raw material in pharmaceutical industry, whether in developed or developing countries. Brazil is privileged regarding to this aspect, as it presents a large biodiversity of flora and fauna, featuring an important differentiator for the development of medicines. The object of study of this present research comprises the leaves of Pimenta pseudocaryophyllus (Gomes) L.R. Landrum, Myrtaceae, popularly known as craveiro-do-mato, louro-cravo or chá de bugre. The objective of this work was to analyze the chemical composition of the essential oil of P. pseudocaryophyllus and assess their antimicrobial properties to bacteria from the oral cavity. The essential oil is obtained from the leaves by hidrodestilation in Clevenger equipment. The analysis of the components was performed by gas chromatography coupled to mass spectrometry (GC-MS); and the antimicrobial activity was verified through the broth macrodilution method for determining the Minimum Inhibitory Concentration (CMI) front of microorganisms Pseudomonas aeruginosa, Staphylococcus aureus and Enterococcus faecalis. The analysis of the chemical composition of the leaves of P. pseudocaryophyllus (Gomes) L.R. Landrum resulted in the identification of 30 components, including eugenol; cineole and the limonene were majority substances of its composition. The results obtained in the disk test broadcast showed an inhibition halo only for S. aureus. In the macrodilution test, the essential oil from leaves of P. pseudocaryophyllus showed antimicrobial activity for S. aureus and E. faecalis in concentration of 20% v/v and for P. aeruginosa in this concentration there was no inhibition. The results found in this experiment contribute and lead to too much research to the development of herbal remedies in the dental area.